Assessment of hydropower potential of the Tisza river basin - Obodovskiy, Oleksandr; Danko, Kostiantyn; Pochaievets, Olena (Journal of Education, Health and Sport, 2017)
The results of calculating the total and ecofriendly hydropower potential of the rivers of the Tisza River Basin within Ukraine are represented in the paper. Total hydropower potential at 114 streams with length of 10 km in the main sub-basin of Tisza has been calculated. The boundaries of the areas (parts) potential with the change of hydraulic characteristics of channels to assess hydropower were identified. The value of ecofriendly hydropower potential was installed. Parts within protected areas and the value of the average flow of water which is less than 0.71 m3/s, which typical for upper parts of the rivers of calculations were excluded.